Fibroblast growth factor 15/19 expression, regulation, and function: An overview. (15th May 2022) - Guthrie, Greg; Vonderohe, Caitlin; Burrin, Douglas
Abstract: Since the discovery of fibroblast growth factor (FGF)-19 over 20 years ago, our understanding of the peptide and its role in human biology has moved forward significantly. A member of a superfamily of paracrine growth factors regulating embryonic development, FGF19 is unique in that it is a dietary-responsive endocrine hormone linked with bile acid homeostasis, glucose and lipid metabolism, energy expenditure, and protein synthesis during the fed to fasted state. FGF19 achieves this through targeting multiple tissues and signaling pathways within those tissues. The diverse functional capabilities of FGF19 is due to the unique structural characteristics of the protein and its receptor binding in various cell types. This review will cover the current literature on the protein FGF19, its target receptors, and the biological pathways they target through unique signaling cascades.